Evaluation of NTRK Gene Fusion by Five Different Platforms in Triple-Negative Breast Carcinoma - Wu, Shafei; Shi, Xiaohua; Ren, Xinyu; Li, Kaimi; Pang, Junyi; Liang, Zhiyong (Frontiers in Molecular Biosciences, 2021)
Triple-negative breast carcinoma (TNBC) is an aggressive disease that has a poor prognosis since it lacks effective treatment methods. Neurotrophic tyrosine receptor kinase (NTRK) fusion genes are excellent candidates for targeted RTK inhibitor therapies and there are available targeted therapy drugs for the treatment of TRK fusion-positive tumors in a tumor agnostic pattern. Our study was designed to investigate the NTRK gene fusion status in TNBC patients and to determine whether RTK-targeted therapies are suitable for TNBC patients.A total of 305 TNBC patients were enrolled in our study. IHC was employed as a prescreening method, and IHC positive cases were further submitted for evaluation by FISH, RT-PCR, and NGS methods.NTRK IHC was evaluated successfully in 287 of the 305 cases, and there were 32 (11.15%) positive cases. FISH was carried out in the 32 IHC positive cases. There were 13 FISH-positive cases if the threshold was set as >15% of the 100 counted tumor cells having a split orange and green signal with more than one signal diameter. There were only 2 FISH-positive cases if the cutoff value was defined as >15% of the counted tumor cells having a split signal with more than two signal diameter widths. One of the FISH-positive cases had a separate NTRK3 FISH signal in 88% of the tumor cells, and its IHC result was strong nuclear staining in all the tumor cells. After evaluation of the morphology, it was re-diagnosed as secretory breast carcinoma, and the NGS result confirmed that it had an NTRK3-ETV6 fusion gene. The other FISH-positive cases were all negative for NTRK gene fusion in the NGS or RT-PCR examination. The NTRK gene fusion rate was low in our TNBC cohort.NTRK gene fusion may be a rare event in TNBC. The high false-positive rate of NTRK gene fusion detected by IHC questions its role as a prescreening method in TNBC. More data may be needed to determine a suitable threshold for NTRK FISH in TNBC in the future. More studies are needed to confirm whether RTK-targeted therapies are appropriate treatments for TNBC patients.